DNA MARKERS CHARACTERISTICS OF RAM HOGS OF MEAT-LARD BREEDS (GROWTH, DEVELOPMENT AND MEAT PRODUCTIVITY) - Yuldashbayev Yusupzhan Artykovich,; Mukhanov Nurlan Buribaevich,; Kudiyarov Rakhim Iskendirovich,; Kozhamuratov Nyshanali Zhadilovich,; Traisov Baluash Bakishevich,; Karynbayev Amanbay Kambarbekovich, (Scientific Journal of Pedagogy and Economics, 2019)
The article presents the results of studying the growth, development and meat productivity of meatlard ram hogs, as well as the presence of gene polymorphism in meat-lard sheep. As a result of studies aimed at investigating the role of marker assessment of sheep, there were obtained data on the frequency of occurrence of genotypes in the two studied genes associated with the growth rate and meat quality of sheep. It was found that in the studied sample of sheep, the GH2 and 1(IGF1) genes were polymorphic. The presence of associations of various genetic variations with one or another level of the studied traits was revealed. During the experiment, the growth and development of young meat-lard ram hogs from birth to 12 months of age were monitored by weighing and linear analysis, taking into account the dynamics of changes in live weight and exterior indicators. It was established that young animals of both breeds had the highest growth energy in the first month and at the time of weaning. The smallest weight gain was between 4 and 7 months of age, i.e. during the feeding season. At the age of 12 months, the Edilbay sheep had a live weight of 61.1 kg, which is 5.7 kg or 9.7% higher than that of young Kazakh fat-tailed ones. Gimmers of Edilbay breed had a similar advantage. So, at the same age, the difference in favor of gimmers of Edilbay breed was 4.8 kg or 10.1%. The results of the control slaughter of one-year-old rams showed the presence of certain interbreed differences in the main indicators. In terms of pre-slaughter weight, young Edilbay sheep exceeded their peers - the Kazakh fattailed breed by 9.9%, and by carcass weight without a fat tail by 11.7%. The slaughter yield was: in the Edilbay breed - 49.9, in the Kazakh fat-tailed breed - 48.6%, which is 2.7% lower. The unequal content of protein and fat in the meat led to different calorific values: higher - 215.6 kcal in Edilbay sheep, and 207.2 kcal in young sheep of the Kazakh fat-tailed breed, which is 3.9% lower. Morphobiochemical analysis showed that, in general, blood parameters in young animals of both breeds were within the physiological standards.